Strategies For Protection Of Violence Against Children Through The Aisyiyah Love of Children (Gaca) Movement In Aba Branch Kindergarten, Mamajang, Makassar - Amirah Amirah; Maria Ulviani; St Muthahharah (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Children are the age group that needs guidance and teaching from adults. Furthermore, the growth and development of children must be protected from aspects of violence, especially